ANALISIS HUBUNGAN SERTIFIKASI ISO 9000 DENGAN EARNING PER SHARE (EPS) PERUSAHAAN MAKANAN DAN MINUMAN DI INDONESIA - Yuliana, Indah (Fakultas Ekonomi, UIN Maliki Malang, 2009)
Pursuant to analysis result of research, hence can be pulled conclusion as follows:Mean of percentage of company which don't have ISO certification 9000 experiencing of increase equal to 27,21% the increase smaller relative in comparison with the percentage of mean increase of sale of company which have had certificate of ISO 9000. But that increase do not enjoy by all companies owning certification. Company owning ISO certification 9000 year 1994 having the percentage of biggest improvement that is 63, 51%. Company getting ISO certification 9000 for year 1995 experiencing of the percentage of improvement equal to 9,99% and also for company which have got ISO certification 9000 for year 1996 experiencing of the percentage of degradation equal to - 0,69%.Pursuant to analysis of ANOVA known that there are difference of EPS of company which do not have ISO 9000 with company getting ISO 9000 year 1994, 1995 and 1996.Pursuant to result test Duncan can know that fourth above company category can be differentiated to become two group, first group of company getting ISO 1996, 1995 and which do not get ISO certification 9000. This matter is caused by company which don't have ISO certification 9000 ( Mayora INDO, fresh of sea, Industrial Ultra Djaya Milk, Ades Alfindo, Endless Davomas and Multifarious Prasidina of Commercial) and company getting ISO 9000 year 1995 and 1996 owning average value of earning per share the nearbyness or one group.while second group is company which do not get ISO certification 9000 and company getting ISO 1994. Matter this means there are some companies which not yet got ISO 9000 but have value of ESP the highness that is company of Delta of Djakarta and of Multi Star of INDO.Pursuant to correlation analysis of rank spearmen's known that earning per company share have relation with ISO certification 9000 (for company getting ISO certification 9000 in the year 1994).